Strong magnetic field dependence of critical current densities and vortex activation energies in an anisotropic clean MgB2 thin film - Kim, Jeehoon (2015)
We report the influence of two-band superconductivity on the flux creep and the critical current densities of a MgB2 thin film. The small magnetic penetration depth of λ=50±10 nm at T=4 K is related to a clean π-band. We find a high self-field critical current density Jc, which is strongly reduced with applied magnetic field, and attribute this to suppression of the superconductivity in the π-band. The temperature dependence of the creep rate S (T) at low magnetic field can be explained by a simple Anderson-Kim mechanism. The system shows high pinning energies at low field that are strongly suppressed by high field.